OS DESAFIOS DO ACESSO E DA PERMANÊNCIA DE PESSOAS COM NECESSIDADES EDUCACIONAIS ESPECIAIS NAS INSTITUIÇÕES DE EDUCAÇÃO SUPERIOR DE SÃO LUIS-MA - Chahini, Thelma Helena Costa (2006)
In the present study the main challenges are analyzed to be surpassed so that pupils with visual deficiency, auditory and physical they have access, permanence and attendance specialized in the Institutions of Higher Education of São Luis-Ma (IES-MA), in accordance with the effective federal legislation. Exactly having its rights assured for the Brazilian Federal Constitution (1988), the people with educational necessities special (NEE) do not have the guarantee of the same ones. Of a poor fraction of the related pupils who come receiving some form educational attendance "especial", the majority does not obtain to arrive at the Higher Education.